Zdravstveni absentizem v sistemu agencijskega dela v Sloveniji - Bitenc, Žiga (Podjetje in delo, 2023)
Slovenia has been grappling with a significant issue concerning sickness absenteeism, consistently ranking among the EU countries with the highest number of working days lost per employee. This matter has been widely recognised as a serious social and legal problem by the Slovenian scientific and professional community. However, the characteristics of the employment relationship greatly influence the nature of this problem for individual employees. Extensive research has shed light on a noteworthy distinction between workers with temporary contracts and those with permanent employment. Studies have revealed that individuals with unstable, non-permanent positions exhibit significantly lower rates of absenteeism compared to their permanently employed counterparts within the same organisation. This observation raises important concerns about the differences in sickness absenteeism between permanent workers and posted (agency) workers. A survey conducted across thirty Slovenian medium and large-sized companies has revealed that permanently employed workers experienced an annual absenteeism rate that was 2.71 percentage points higher than that of agency workers over a span of five calendar years. The lower absenteeism rate among agency workers can be attributed to a complex combination of factors: agency workers tend to work more diligently and remain consistently present at the workplace, sometimes even when they are unwell. Such behaviour stems from their desire to be recognised by superiors as promising candidates, increasing their chances of securing a permanent position with the user company. Nevertheless, this phenomenon can also lead to burnout, lack of commitment, and negative attitudes towards work. It is imperative that agencies and companies foster a non-discriminatory approach when dealing with posted workers. This includes implementing measures that prioritise the well-being, health, and safety of all employees in the workplace.
Keywords: agencijski delavci; agencijsko delo; bolniške odsotnosti; bolniški stalež; delo; delovni pogoji; delovno pravo; diskriminacija; napoteni delavci; Slovenija; zaposleni